МОЖЛИВОСТІ ВИКОРИСТАННЯ ТЕХНОЛОГІЙ ГІС ТА ДЗЗ ПРИ ЕКОЛОГІЧНОМУ МОНІТОРИНГУ МАКУХІВСЬКОГО СМІТТЄЗВАЛИЩА В ПОЛТАВСЬКІЙ ОБЛАСТІ - Shevchuk, S.; Pudenko, O. (Scientific Progress & Innovations, 2022)
Makukhivka dump has been functioning since 1953. According to the methods of audit assessment of the environmental danger of municipal solid waste (MSW) grounds and dumps, this object has exhausted all possible resources, is overloaded, and belongs to the group of extremely dangerous. Unsatisfactory condition of the natural complex in the dump’s zone is connected with the fact that the place of waste disposal does not correspond to the sanitary and hygienic standards, it has no filtration screen, filtrate purification and removal system; it has been operated without using preventive and reliable measures for groundwater isolation. The use of geo-informational systems (GIS) and remote land sounding (RLS) methods allowed to monitor the dump’s territory with implementing the following stages: distinguishing the territory; spectral characteristics of natural objects; establishing the biggest differences and classification of the dump’s surface images; conducting different time comparison of the received raster pictures and composing thematic maps and diagrams of the dump’s effect on the environment; finding out the ground’s increase in the area and the lack of correspondence between the satellite photographs and the data of regulatory documents; establishing the dependence of fires starting on the dump’s territory upon the concentration of the dump gases in the atmosphere. To assess the ecological condition of Makukhivka dump, the GIS functional cross-platform was applied, namely, Quantum GIS (QGIS) 3.16., and its supplements: Dzetsaka; MapSwipeTool; QvickMapServices. The photographs of low and medium distribution capacity from 10 to 30 m were analyzed as well as multi-spectral ones (up to 12 channels depending on the year of receiving), and those got from satellites:Sentinel 2 L2A of July 15,2021 with using channels 12, 11, 8; Landsat 8 L2 of June 14, 2013 (channels 2,3,4, and 5); Landsat 4-5 TM L2 of July 12, 2000 (channels 1,2,3); Sentinel 5P. The studies of Makukhivka dump as a result of human anthropogenic activity were presented in the paper. The attempt was made to evaluate several characteristics of the MSW ground by means of GIS and RLS, and substantiate measures to increase environmental security in the zone of the dump’s impact. The research results present the conducted environmental assessment of Makukhivka dump territory taking into account constant and emergency environmental risks; the comparative analysis of the ground’s characteristics was made (total area, the peculiarities of soil-plant cover, some indicators of atmospheric air) using RLS means during the period from 2000 to 2021; the measures aimed at decreasing the level of the dump’s environmental danger were proposed.